2010
DOI: 10.1093/nar/gkq1216
|View full text |Cite
|
Sign up to set email alerts
|

Cell stress is related to re-localization of Argonaute 2 and to decreased RNA interference in human cells

Abstract: Various kinds of stress on human cells induce the formation of endogenous stress granules (SGs). Human Argonaute 2 (hAgo2), the catalytic core component of the RNA-induced silencing complex (RISC), can be recruited to SGs as well as P-bodies (PBs) indicating that the dynamic intracellular distribution of hAgo2 in SGs, in PBs or at other sub-cellular sites could be related to the efficiency of the RNA interference (RNAi) machinery. Here, we studied the influence of heat shock, sodium arsenite (NaAsO2), cyclohex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 59 publications
4
59
0
Order By: Relevance
“…Upon cellular stress induced by arsenite, both Ago2 and TIA-1, a stress granule (SG)-specific marker, are recruited to SGs involved in translation inhibition (Fig. 1D) (4,18,19). By IFA staining of Ago2 and TIA-1 in arsenite-treated HeLa cells, we found that both cytoplasmic Ago2 and TIA-1, but not nuclear Ago2 and TIA-1, are co-stained in numerous cytoplasmic SGs (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Upon cellular stress induced by arsenite, both Ago2 and TIA-1, a stress granule (SG)-specific marker, are recruited to SGs involved in translation inhibition (Fig. 1D) (4,18,19). By IFA staining of Ago2 and TIA-1 in arsenite-treated HeLa cells, we found that both cytoplasmic Ago2 and TIA-1, but not nuclear Ago2 and TIA-1, are co-stained in numerous cytoplasmic SGs (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Indeed, nuclear proteins are more resistant to knockdown mediated by shRNA because of the reduced availability of RNAi cellular machinery into the nucleus. 70 In contrast, Cavin-1 downregulation in RH30 cells did not affect the subcellular localization of Cav-1 (Figure 6b, bottom panels). We next assayed the cell proliferation, migration and chemoresistance of the different clones by means of the Crystal violet, Boyden chamber and Neutral Red assays, respectively.…”
Section: Cavin-1 Knockdown Decreases Cell Proliferation and Migrationmentioning
confidence: 85%
“…Since Dicers and Argonautes can associate with tRNA-derived sequences [24,25], it follows that specific stress conditions might favor such association. Ago-2 has been found in stress granules, which also correlated with decreased RNAi in human cells [26]. In addition, Drosophila Ago-2 loading with specific small RNAs has been shown to increase after heat shock [27].…”
Section: Trna Modifications Can Affect Trna Fragmentationmentioning
confidence: 94%